Minimal fresh gas flow sevoflurane anesthesia and postoperative acute kidney injury in on-pump cardiac surgery: a randomized comparative trial - Lineburger, Eric Benedet; Módolo, Norma Sueli Pinheiro [UNESP]; Braz, Leandro Gobbo [UNESP]; do Nascimento, Paulo [UNESP] (Elsevier, 2022)
Background: Compound A is generated by sevoflurane when it reacts with carbon dioxide absorbers with strong bases at minimal fresh gas flow (FGF) and is nephrotoxic in animals. No conclusive data has shown increased risk in humans. The aim of this study was to investigate if minimal FGF promotes an increase in the incidence of acute kidney injury (AKI) when compared to high FGF in patients undergoing on-pump cardiac surgery under sevoflurane anesthesia. Methods: Two hundred and four adult patients scheduled for on-pump cardiac surgery under sevoflurane anesthesia were randomly allocated to two groups differentiated by FGF: minimal FGF (0.5 L.min−1) or high FGF (2.0 L.min−1). Baseline creatinine measured before surgery was compared daily to values assayed on the first five postoperative days, and 24-hour urinary output was monitored, according to the KDIGO (Kidney Disease Improving Global Outcomes) guideline to define postoperative cardiac surgery-associated acute kidney injury (CSA-AKI). Creatinine measurements were also obtained 20 and 120 days after hospital discharge. Results: Postoperative AKI occurred in 55 patients, 26 patients (29.5%) in the minimal FGF group and 29 patients (31.5%) in the high FGF group (p = 0.774). Twenty days after discharge, 11 patients (6.1%) still had CSA-AKI and 120 days after discharge only 2 patients (1.6%) still had CSA-AKI. Conclusions: When compared to high FGF, minimal FGF sevoflurane anesthesia during on-pump cardiac surgery is not associated with increased risk of postoperative AKI in this population at high risk for renal injury.
Keywords: Acute kidney injury; Anesthesia; Occupational health; Sevoflurane